Turkey : Financial Sector Assessment Program-Detailed Assessment of Observance of the Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2017)
This paper presents an assessment of observance of Basel Core Principles for Effective Banking Supervision in Turkey. Since the previous assessment conducted in 2011, the Banking Regulation and Supervisory Agency has made several significant improvements to its supervisory framework. There are areas that still warrant improvement, including addressing legal provisions that undermines supervisory independence, providing a deeper risk assessment focus to supervisory inspections and follow up, enhancing the forward-looking component of the assessments, streamlining risk management and corporate governance requirements, strengthening the supervisory enforcement regime, demanding recovery plans, developing group resolution plans, and increasing the ability to act at an early stage to address unsafe and unsound practices.